Establishing the most effective way to deliver the sketch procedure to enhance interviewee free recall - Eastwood, Joseph (Psychology, crime & law, 2019)
The relative effectiveness of three sketching procedures for enhancing the recall of a witnessed event was assessed. Participants (N = 123) viewed a mock crime video and were asked to recall its contents using one of three sketching procedures (i.e. Sketch and Free Recall; Sketch then Free Recall; Sketch and Explain then Free Recall) or two comparison procedures (i.e. Mental Reinstatement of Context; Control). Participants who were administered the Sketch and Explain then Free Recall procedure recalled more correct details than those who were administered the other four procedures (all ds > 0.70); the greater number of correct details was observed primarily for object and action details. There was minimal difference in incorrect details recalled or accuracy rate between all five procedures. The implications of using different sketching procedures for enhancing recall at the onset of investigative interviews are discussed.